Extent of credit card fraud in the hotel industry in Kenya - Yego, Peninah Cherono (Strathmore University, 2014)
This research was conducted with the main objective of establishing the extent of credit card fraud in the Hotel industry in Kenya. The research sought to establish the impact of credit card fraud to this industry, factors that contribute to the fraud and measures that the industry players are taking to address it. The research targeted four and five star hotels in Nairobi, which primarily are target for business and leisure travellers. The empirical study was conducted in a sample of 20 hotels, out of a target population of 25 hotels in Nairobi, Kenya. The target response comprised of the hotel Finance Managers, Information Technology Managers, Credit Control Managers and Internal Auditors. The research adopted both a descriptive and explanatory research design; data obtained was analyzed using descriptive statistics. The analytical results showed increased acceptance of credit cards as a mode of payments in the hotels. However, fear of fraudulent charges still keeps the clients from using their cards. The respondents placed the financial loss as a result of credit card fraud between Ksh. 0-5 Million annually. It was however seen that fear of damaged hotel reputation is of more concern to the hotels than the financial loss. The study also showed that lost or stolen cards, identity theft, counterfeit credit cards and the internet are common factors that contribute to credit card fraud in hotels. The respondents additionally pointed out hotel cashier's indirect theft from card paying guests as another way through which card fraud occurs in the hotels. Most respondents indicated that full implementation of the Payment Card Industry Data Security Standards (PCI DSS) was the optimal way for the Hotel industry to mitigate against credit card fraud; this includes ensuring optimal security of client data held or interacted with at the hotels. These measures are already being implemented by some hotels, although still at the initial stages.
Submitted in partial fulfillment of the requirements for the Degree of Master of Commerce
Keywords: Fraud; Credit card fraud; Hotel industry; Kenya; Theft